2004
DOI: 10.1210/en.2004-0263
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Transgenic Melanocyte-Stimulating Hormone Overexpression in Lean and Obese Mice

Abstract: The proopiomelanocortin-derived peptide, alpha-MSH, inhibits feeding via melanocortin receptors in the hypothalamus and genetic defects inactivating the melanocortin system have been shown to lead to obesity in experimental animals and humans. To determine whether long-term melanocortinergic activation has significant effects on body weight and composition and insulin sensitivity, transgenic mice overexpressing N-terminal proopiomelanocortin, including alpha- and gamma(3)-MSH, under the control of the cytomega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 51 publications
6
52
0
Order By: Relevance
“…Considering this notion, the orexigenic pathway(s) are programmed to prevent anorexia in lean animals and should readily overcome a mild anorectic stimulus such as that exerted by rAAV-Pomc treatment. Our findings are consistent with two previous reports in which transgenic overproduction of POMC-derived peptides in mice did not alter food intake in lean mice [31,32]. Despite the lack of anorexia in the present study, there is evidence that POMC affects the overall central melanocortin system.…”
Section: Discussionsupporting
confidence: 93%
“…Considering this notion, the orexigenic pathway(s) are programmed to prevent anorexia in lean animals and should readily overcome a mild anorectic stimulus such as that exerted by rAAV-Pomc treatment. Our findings are consistent with two previous reports in which transgenic overproduction of POMC-derived peptides in mice did not alter food intake in lean mice [31,32]. Despite the lack of anorexia in the present study, there is evidence that POMC affects the overall central melanocortin system.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study, a serotype 2 rAAVPomc vector also markedly stimulated brown adipose tissue thermogenesis in obese Zucker rats 38 days after vector delivery [22]. Moreover, transgenic MSH overexpression in lean and obese db/db mice reduced weight gain and adiposity without affecting food intake [39]. Although lacking direct evidence of whole-body energy expenditure, we suggest that, in addition to the hypophagia, an increase in energy expenditure, such as fat oxidation within brown adipose tissue, white adipose tissue or muscle, contributed to the amelioration of body weight and fat in aged obese rats following central Pomc gene therapy and, in particular, was instrumental in maintaining the lost weight after the anorexia attenuated.…”
Section: Discussionmentioning
confidence: 80%
“…Significantly, the hyperinsulinemia in Mc4r Ϫ/Ϫ mice precedes the onset of hyperphagia and obesity (32). Transgenic overexpression of neuronal POMC peptides in leptindeficient ob/ob mice (36) and yellow agouti A y /a mice (37) can significantly ameliorate hyperglycemia and insulin resistance by enhancing peripheral insulin sensitivity, independent of effects on food intake and body weight. Pharmacological studies have also shown that central administration of ␣-melanocyte-stimulating hormone can increase both insulin-stimulated glucose disposal and insulin-induced suppression of hepatic gluconeogenesis (33,34).…”
Section: Ap Coll and Associatesmentioning
confidence: 99%